SRGP-1/srGAP and AFD-1/afadin stabilize HMP-1/⍺-catenin at rosettes to seal internalization sites following gastrulation in C. elegans. - Joel M Serre; Mark M Slabodnick; Bob Goldstein; Jeff Hardin (PLoS Genetics, 2023)
A hallmark of gastrulation is the establishment of germ layers by internalization of cells initially on the exterior. In C. elegans the end of gastrulation is marked by the closure of the ventral cleft, a structure formed as cells internalize during gastrulation, and the subsequent rearrangement of adjacent neuroblasts that remain on the surface. We found that a nonsense allele of srgp-1/srGAP leads to 10-15% cleft closure failure. Deletion of the SRGP-1/srGAP C-terminal domain led to a comparable rate of cleft closure failure, whereas deletion of the N-terminal F-BAR region resulted in milder defects. Loss of the SRGP-1/srGAP C-terminus or F-BAR domain results in defects in rosette formation and defective clustering of HMP-1/⍺-catenin in surface cells during cleft closure. A mutant form of HMP-1/⍺-catenin with an open M domain can suppress cleft closure defects in srgp-1 mutant backgrounds, suggesting that this mutation acts as a gain-of-function allele. Since SRGP-1 binding to HMP-1/⍺-catenin is not favored in this case, we sought another HMP-1 interactor that might be recruited when HMP-1/⍺-catenin is constitutively open. A good candidate is AFD-1/afadin, which genetically interacts with cadherin-based adhesion later during embryonic elongation. AFD-1/afadin is prominently expressed at the vertex of neuroblast rosettes in wildtype, and depletion of AFD-1/afadin increases cleft closure defects in srgp-1/srGAP and hmp-1R551/554A/⍺-catenin backgrounds. We propose that SRGP-1/srGAP promotes nascent junction formation in rosettes; as junctions mature and sustain higher levels of tension, the M domain of HMP-1/⍺-catenin opens, allowing maturing junctions to transition from recruitment of SRGP-1/srGAP to AFD-1/afadin. Our work identifies new roles for ⍺-catenin interactors during a process crucial to metazoan development.